Investigating the Relationship of Organizational Citizenship Behavior with Job Satisfaction, Organizational Commitment and Turnover Intention: Evidence from the Banking Sector of Pakistan (Global Journal of Management and Business Research, 2016)
Organizational Citizenship Behaviors(OCB) are those behaviors for which employees are neither rewarded by their organizations, nor employees are encouraged to show such behaviors. OCB has potential to make countless contribution towards organizational effectiveness. The purpose of this study is to investigate the relationship between jobsatisfaction, organizational commitment, OCB and turnover intentions. This study has been conducted in the banking sector and for this purpose responses from 140 public and private banks#x2019; employees were obtained through simple random sampling. A questionnaire was used as a data collection instrument. SPSS17.0 software was used to analyze the data. Findings revealed that OCB is positively correlated with job satisfaction and organizational commitment, whereas it is negatively correlated with the turnover intentions.
Keywords: OCB; jobsatisfaction; organizational commit-ment; turnover intensions; banks